FOOD FULFILLMENT FOR CHILDREN UNDER FIVE BY FAMILY IN DISASTER RESERVE AREA - Darwis, Rudi Saprudin; Nurseto, Hardian Eko; Andoyo, Robi; Sukri, Nandi; Hadi, Bambang Nur; Huda, Syamsul; Triani, Rini (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2018)
The ability of families to meet the food needs becomes one of the determining factors in the fulfillment of food of children under five. For the communities living in disaster areas, the situation can be further complicated by the conditions of the natural environment damaged by the disaster. This research describes the fulfillment of food of children under five, especially those aged between three to five years, by families who lived in disaster-prone areas. This research was conducted in Nagrakjaya Village, Curug kembar Subdistrict, Sukabumi Regency which is prone to earth movement disaster and part of its territory is considered as the red zone. The research employed a qualitative method using data obtained from parents informant of children under five, health cares, and community leaders. The aspects covered in this study were: food access, food availability, consumption pattern, coping strategy food, and food preparedness. The results showed that in terms of access to food, people obtained their foodstuffs depending on what was available to mobile vendors and small shops regardless of their financial ability to obtain food. Moreover, people did not provide special foods for toddlers. In dealing with difficult situations during the event of a disaster, people reliedon the provision of food from fellow citizens or small shop owners and outside help. People also felt no need to store food supplies for the possibility of difficult situations, both for adults and toddlers, even though toddlers have a different consumption pattern to adults and require balanced nutritional needs.As a recommendation, it is necessary to conduct campaigns and dissemination of healthy food for children under five to increase parents knowledge about healthy consumption for children under five, especially in the disaster-prone areas.